(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
According to the WHO, iron deficiency anemia suffers from more than 30% of the world’s population, most of whom are women and children . The prevalence of anemia largely depends on the standard of living, nutrition of the population, the quality and availability of medical care. Correct diagnosis, including conducting various laboratory tests, allows you to identify this pathology in time and choose the appropriate treatment method. Anemia is considered a problem of maintaining public health and affects the population of the whole world.